Pelaksanaan Senam Sehat Bagi Anak Usia Dini di PAUD Patryadira Desa Kalikesur - Sufyan, Muhammad Ali; Handayani, Rahmaya Nova; Setianingsih, Sitti; Suandika, Made; A, M Aryadi; Agus, Dwi (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
Patryadira Early Childhood Education (PAUD) is one of the PAUD playgroup schools located in Kalikesur Village, Kedungbanteng District. A total of 25 children participated in healthy gymnastics activities, which aim to maintain their health. The community service program carried out at PAUD Patryadira Kalikesur Village aims to improve children's motor skills through healthy gymnastics. This activity was organized by UHB 2025 KKN students in collaboration with the Principal of Patryadira PAUD. The results obtained from this activity show that healthy gymnastics movements can improve children's motor skills at PAUD Patryadira, as well as help teachers in overcoming various problems that exist in schools.